Disrupted sleep–wake regulation in type 1 equilibrative nucleoside transporter knockout mice. (10th September 2015) - Kim, T.; Ramesh, V.; Dworak, M.; Choi, D.-S.; McCarley, R.W.; Kalinchuk, A.V.; Basheer, R.
Graphical abstract: Highlights: Equilibrative nucleoside transporter 1 (ENT1) knockout mice have decreased non-rapid eye movement sleep (NREMS). ENT1 mice display a weak correlation between the hourly Wake EEG theta (Wθ) and NREMS delta (NRδ) of subsequent hour. Adenosine infusion into basal forebrain restores the Wθ–NRδ correlation and NREMS. ENT1 knockout mice show normal homeostatic sleep response following sleep deprivation. Data suggest a differential regulation of adenosine during spontaneous and homeostatic sleep. Abstract: The type 1 equilibrative nucleoside transporter (ENT1) is implicated in regulating levels of extracellular adenosine ([AD]ex ). In the basal forebrain (BF) levels of [AD]ex increase during wakefulness and closely correspond to the increases in the electroencephalogram (EEG) delta (0.75–4.5 Hz) activity (NRδ) during subsequent non-rapid eye movement sleep (NREMS). Thus in the BF, [AD]ex serves as a biochemical marker of sleep homeostasis. Waking EEG activity in theta range (5–9 Hz, Wθ) is also described as a marker of sleep homeostasis. An hour-by-hour temporal relationship between the Wθ and NRδ is unclear. In this study we examined the relationship between these EEG markers of sleep homeostasis during spontaneous sleep–wakefulness and during sleep deprivation (SD) and recovery sleep in the ENT1 gene knockout (ENT1KO) mouse. We observed that baseline NREMS amount was decreased during the light period in ENT1KO mice, accompanied by a weak correlation between Wθ of each hour and NRδ of its subsequent hour when compared to their wild-type (WT) littermates. Perfusion of low dose of adenosine into BF not only strengthened the Wθ–NRδ relationship, but also increased NREMS to match with the WT littermates suggesting decreased [AD]ex in ENT1KO mice. However, the SD-induced [AD]ex increase in the BF and the linear correlation between the EEG markers of sleep homeostasis were unaffected in ENT1KO mice suggesting that during SD, sources other than ENT1 contribute to increase in [AD]ex. Our data provide evidence for a differential regulation of wakefulness-associated [AD]ex during spontaneous vs prolonged waking.